The Soul of Supervision: Counselor Spirituality. Issue 1 (April 2017) - Garner, Curtis M.; Webb, L. Kay; Chaffin, Carol; Byars, Allyn
Abstract : Because spirituality training for counselors and supervisors is vital to counselor development, the authors examined the relationships between purpose in life, the integration of spirituality into supervision, and the supervisory working alliance among a sample of supervisors and trainees. Supervisors reported a greater sense of purpose and spiritual discussion during supervision than trainees. Trainees' personal sense of purpose was positively related to spiritual discussions with a supervisor and to an emphasis on client issues in supervision.